Analytic and solid geometry : made easy - Comandante, Jr., Felipe L. (Mandaluyong City, Philippines : National Book Store, 2008)
The author's major objective throughout the writing of this textbook-workbook is to present the analytic and solid geometry to engineering and computer science students in a simple and understandable language.
Chapter 1. Fundamental Concepts -- Chapter 2. The Line -- Chapter 3.The Circle -- Chapter 4.Conic Sections -- Chapter 5. Polar Coordinates and Parametric Equations -- Chapter 6. Space Coordinates and Surfaces -- Chapter 7. Mensuration of Plane and Solid Figures.
Keywords: ANALYTIC -- GEOMETRY